Investigating the glueball-like particle X(2370) in B meson decays - Xiao-Tong Li; Guang-Yu Wang; Qi-An Zhang (European Physical Journal C: Particles and Fields)
Abstract Based on the collected data on $$J/\psi \rightarrow \gamma K_S^0K_S^0\eta '$$ J / ψ → γ K S 0 K S 0 η ′ , the Beijing Spectrometer (BESIII) experiment has conducted an analysis of the mass and spin parity of the X(2370) particle. The findings areconsistent with the characteristics expected of the lightest pseudoscalar glueball. We point out that further exploration of this particle’s nature can be pursued through investigations of heavy bottom meson decays. Assuming the identity of X(2370) as a pseudoscalar glueball, we compute the form factors for $$B\rightarrow X(2370)$$ B → X ( 2370 ) transitions in the factorization approach. With these results, the estimated branching fractions for semileptonic B decays into X(2370) can reach the order of $$10^{-6}$$ 10 - 6 and those for nonleptonic decays can reach the order $$10^{-8}$$ 10 - 8 . These results suggest that decays of B mesons into X(2370) are detectable at experimental facilities like Belle-II. Future experimental endeavors hold promise in expanding our understanding of glueball physics, contributing to the ongoing exploration of this intriguing particle.